Composite System of 3D-Printed Polymer and Acellular Matrix Hydrogel to Repair Temporomandibular Joint Disc - Yi, Ping; Liang, Jiadi; Huang, Futing; Zhao, Zuodong; Zhou, Xiaohui; Gao, Qianya; Huang, Min; Chen, Baoyi; Guo, Zhenzhao; Liu, Chang (Frontiers in Materials, 2021)
Tissue engineering is a promising approach to restore or replace a damaged temporomandibular joint (TMJ) disc. However, constructing a scaffold that can mimic biomechanical and biological properties of the natural TMJ disc remains a challenge. In this study, three-dimensional (3D) printing technology was used to fabricate polycaprolactone (PCL)/polyurethane (PU) scaffolds and PU scaffolds to imitate region-specific biomechanical property of the TMJ disc. The scaffolds were coated with polydopamine (PDA) and combined with decellularized matrix (dECM). Then, rat costal chondrocytes and mouse L929 fibroblasts, respectively, were suspended on the composite scaffolds and the biological functions of the cells were studied. The properties of the scaffolds were characterized by scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), contact angle analysis, and biomechanical testing. To verify the biocompatibility of the scaffolds, the viability, proliferation, and extracellular matrix (ECM) production of the cells seeded on the scaffolds were assessed by LIVE/DEAD staining, Cell Counting Kit-8 assay, biochemical content analysis, immunofluorescence staining, and qRT-PCR. The functionalized hybrid scaffolds were then implanted into the subcutaneous space of nude mice for 6 weeks, and the regenerated tissue was evaluated by histological staining. The biomechanical properties of PCL/PU and PU scaffolds were comparable to that of the central and peripheral zones, respectively, of native human TMJ disc. The PDA-coated scaffolds displayed superior biomechanical, structural, and functional properties, creating a favorable microenvironment for cell survival, proliferation, ECM production, and tissue regeneration. In conclusion, 3D-printed polymer scaffolds coated with PDA and combined with dECM hydrogel were found to be a promising substitute for TMJ disc tissue engineering.